The EU Cohesion policy in context: regional growth and the influence of agricultural and rural development policies - Riccardo Crescenzi; Mara Giua (London School of Economics and Political Science (LSE), European Institute, 2014)
This paper looks at the Cohesion Policy of the European Union (EU) and investigates how the EU agricultural and rural development policies shape its influence on regional growth. The analysis of the drivers of regional growth shows that the EU Regional Policy has a positive and significant influence on economic growth in all regions. However, its impact is stronger in the most socio-economically advanced areas and is maximised when its expenditure is complemented by Rural Development and Common Agricultural Policy (CAP) funds. The top-down funding of the CAP seems to be able to concentrate some benefits in the most deprived areas. Conversely only the most dynamics rural areas are capable of leveraging on the bottom-up measures of the EU Rural Development Policy. This suggests that EU policy makers in all fields should constantly look for the best mix of bottom-up and top-down measures in order to tackle structural disadvantage.
Keywords: O18; R11; R58; 330; regional policy; European Union; regional growth; rural development; Common Agricultural Policy